The Dynamics of Capital Accumulation in the US: Simulations after Piketty - Philippe De Donder; John E. Roemer (Center for Economic Studies and ifo Institute (CESifo), 2015)
We calibrate a sequence of four nested models to study the dynamics of wealth accumulation. Individuals maximize a utility function whose arguments are consumption and investment. They desire to accumulate wealth for its own sake – this is not a life-cycle model. A competitive firm produces a single good from labor and capital; the rate of return to capital and the wage rate are market-clearing. The second model introduces political lobbying by the wealthy, whose purpose is to reduce the tax rate on capital income. The third model introduces differential rates of return to capitals of different sizes. The fourth model introduces inheritance and intergenerational mobility.
Keywords: D31; D58; E37; 330; Piketty; dynamics of wealth accumulation; intergenerational mobility; Kantian equilibrium